2011
DOI: 10.1002/hup.1253
|View full text |Cite
|
Sign up to set email alerts
|

Who's left? Symptoms of schizophrenia that predict clinical trial dropout

Abstract: A significant proportion of subjects drop out of medium to long-term clinical studies prior to trial completion. This may bias reported study outcomes and reduce the statistical power of analyses. There is therefore a need for researchers to better understand the characteristics of dropout populations to increase completion rates. Data from a set of participants recruited as part of a 24-week placebo-controlled trial were used to determine the relationship between the five Lindenmayer factors of positive, nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The highest drop-out rate was reported by Goff et al (2005) while conducting a 6-month trial in schizophrenia patients with 50mg/d DCS coadministered with conventional antipsychotics. More detailed analysis of the subjects in this study did not show a difference between placebo and verum, reinforcing the theory that the high drop-out rate is not drug related but illness-associated, since long-term studies with schizophrenic patients often have high drop-out rates ( Thompson et al, 2011 ).…”
Section: Safety Aspectssupporting
confidence: 79%
“…The highest drop-out rate was reported by Goff et al (2005) while conducting a 6-month trial in schizophrenia patients with 50mg/d DCS coadministered with conventional antipsychotics. More detailed analysis of the subjects in this study did not show a difference between placebo and verum, reinforcing the theory that the high drop-out rate is not drug related but illness-associated, since long-term studies with schizophrenic patients often have high drop-out rates ( Thompson et al, 2011 ).…”
Section: Safety Aspectssupporting
confidence: 79%
“…Also, 18.5% of the sample did not return for follow-up visits. High attrition is a well-known problem in psychiatric research (Martin et al 2006;Thompson et al 2011;Jorgensen et al 2014). Our attrition after baseline were rather low, and we were able to capture information on medication persistence and reasons for treatment discontinuation in 124 (95.4%) of 130 patients.…”
mentioning
confidence: 85%
“…The FEP sample was large and naturalistic, from different EIS within well-defined catchment areas, with minimal confounding effects of chronicity, institutionalization and prolonged exposure to antipsychotic treatment. Previous studies have indicated that FEP patients with higher NS might be at greater risk of dropping out (AlAqeel & Margolese, 2012;Thompson et al, 2011;Üçok & Ergül, 2014). Thus, although there was a considerable amount of missing data due to the naturalistic follow-up study design, MI was applied in order to correct for biases due to non-completion (Schafer & Graham, 2002).…”
Section: Strengths and Limitationsmentioning
confidence: 99%